Berpikir positif dan efikasi diri pada mahasiswa yang sedang menyusun skripsi - Hidayat, Ahmad; Framita, Nila; Muliadi, Rahmad (Jurnal Psikologi Poseidon, 2024)
Abstract. Students, in completing their thesis, brought up certain reactions, and this was related to positive thinking and self-efficacy. The purpose of this study was to determine the relationship between positive thinking and self-efficacy in students who were preparing a thesis. The sampling technique used was a probability sampling technique with a saturated sampling method. The sample in this study amounted to 150 students and female students who were completing their theses at the Faculty of Psychology, Riau Islamic University (UIR). The data collection method used was a positive thinking scale and a self-efficacy scale that was modified from previous research. The reliability coefficient of the positive thinking scale was 0.865, and the self-efficacy scale was 0.854. Statistical analysis using Spearman's Rho correlation was processed through SPSS version 23.0 for Windows. It was found that there was a positive relationship between positive thinking and self-efficacy (r = 0.275, p = 0.001). This meant that the higher the positive thinking, the higher the self-efficacy; otherwise, the lower the positive thinking, the lower the self-efficacy. Positive thinking and self-efficacy had a relationship and were essential in academic situations, including students who compiled a thesis. It was hoped that students would prioritize themselves and always think positively, especially when doing their final project.